2016
DOI: 10.1186/s12983-016-0155-z
|View full text |Cite
|
Sign up to set email alerts
|

Sea shell diversity and rapidly evolving secretomes: insights into the evolution of biomineralization

Abstract: An external skeleton is an essential part of the body plan of many animals and is thought to be one of the key factors that enabled the great expansion in animal diversity and disparity during the Cambrian explosion. Molluscs are considered ideal to study the evolution of biomineralization because of their diversity of highly complex, robust and patterned shells. The molluscan shell forms externally at the interface of animal and environment, and involves controlled deposition of calcium carbonate within a fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
175
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 142 publications
1
175
0
1
Order By: Relevance
“…Conchiferan shells are layered and often covered by a thin, organic outer layer called the periostracum (Kocot et al 2016). The underlying calcified layers, typically comprising aragonitic or calcite crystals, confer specific physical properties to the shell, and are classified based on their crystalline microstructures [i.e., prismatic, nacreous, crossed lamellar or homogeneous (Chateigner et al 2000; Furuhashi et al 2009)].…”
Section: Introductionmentioning
confidence: 99%
“…Conchiferan shells are layered and often covered by a thin, organic outer layer called the periostracum (Kocot et al 2016). The underlying calcified layers, typically comprising aragonitic or calcite crystals, confer specific physical properties to the shell, and are classified based on their crystalline microstructures [i.e., prismatic, nacreous, crossed lamellar or homogeneous (Chateigner et al 2000; Furuhashi et al 2009)].…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that invertebrate skeletal proteomes include varying fractions of novel proteins -producing no significant matches against DNA sequence databases -and do exhibit contrasting rates of conservation between and within lineages. For instance, about 40% of the skeletal proteome is shared among echinoderms (Flores & Livingston 2017) , while in molluscs the fraction of shared proteins is only about 10% (Kocot et al 2016) .…”
Section: Introductionmentioning
confidence: 99%
“…The model presented here offers a straightforward mechanism for the development of spiral shell sculpture that would be worth testing in other gastropods. Numerous transcriptomic and genetic surveys suggest that the molecular pathways and signaling for shell secretion is complicated, and some components are not very conserved (reviewed in Kocot, Aguilera, McDougall, Jackson, & Degnan, 2016). However, as modern tools and mollusc sampling improves, our ability to understand the formation and evolution shell morphology, both in terms of shell sculpture and shell color (Williams, 2017) improves.…”
Section: Discussionmentioning
confidence: 99%